2020
DOI: 10.1038/s41467-020-17171-y
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis of multidecadal biodiversity trends in Europe

Abstract: Local biodiversity trends over time are likely to be decoupled from global trends, as local processes may compensate or counteract global change. We analyze 161 long-term biological time series (15-91 years) collected across Europe, using a comprehensive dataset comprising 6,200 marine, freshwater and terrestrial taxa. We test whether (i) local long-term biodiversity trends are consistent among biogeoregions, realms and taxonomic groups, and (ii) changes in biodiversity correlate with regional climate and loca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
112
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3
1

Relationship

3
7

Authors

Journals

citations
Cited by 152 publications
(122 citation statements)
references
References 67 publications
8
112
1
1
Order By: Relevance
“…In contrast, the loss of native macroinvertebrates overweighed the gains from non‐native species, and therefore α‐diversity decreased. Our results, therefore, confirm previous considerations that variations in species composition are more informative indicators of changes in biotic communities than α‐diversity metrics (Pilotto et al., 2020).…”
Section: Discussionsupporting
confidence: 91%
“…In contrast, the loss of native macroinvertebrates overweighed the gains from non‐native species, and therefore α‐diversity decreased. Our results, therefore, confirm previous considerations that variations in species composition are more informative indicators of changes in biotic communities than α‐diversity metrics (Pilotto et al., 2020).…”
Section: Discussionsupporting
confidence: 91%
“…Additionally, declining populations may not only be less able to disperse and colonize new areas (fewer individuals that emigrate) but also have a lower potential for adjusting in situ, because of loss of genetic variability (Anderson 2016). Large declines in insect populations have recently been reported, and although these trends vary greatly between regions and taxa (Crossley et al 2020;van Klinket al 2020;Pilotto et al 2020), our results also point to comprehensive population declines among Finnish Lepidoptera as 38.5% of the studied species showed negative population trends.…”
Section: Discussionmentioning
confidence: 99%
“…Their assessment, driven largely by European and North American datasets, suggested terrestrial insects were declining at a rate close to 1% per year, while aquatic insects appeared to be increasing in abundance, again by about 1% per year. Pilotto et al (52) analyzed the abundance, richness, diversity, and faunal turnover for 161 long-term biological time series (15 to 91 y) for more than 6,000 European marine, freshwater, and terrestrial animal and plant taxa; 53 of their datasets were for insects. They found that freshwater insects had increased in diversity (but not abundance).…”
Section: History Of Insect Decline Reportsmentioning
confidence: 99%